Metamorfoses da medicalização e seus impactos na família brasileira - Barbiani, Rosangela; Junges, José Roque; Asquidamine, Fabiane; Sugizaki, Eduardo (IMS-UERJ, 2014)
This paper approaches the cultural, political and social traits of the medicalization phenomenon that has instituted the Brazilian sociability through the education and moralization of the family according to icons of a citizenship hygienist ideology. The study is based on review of historical research, which points to the context of origin of the citizenship notion, associated to social pattern how the hygiene, the expertise knowledge, especially medical and the social control over the family were framing profiles of infants and young suitable for the civilian society. The research analyses the devices that the State used to align emerging public policies to legitimize the biological pattern of sociability in the production of knowledge that ratifies the order placed. Finally the text reflects on the relations between the past and the present, examining the strategic devices of affirmation of the hegemonic ideology of the capitalist regulation on the Brazilian family, through the medicalization of contemporary social life, in its updating dimensions. It is concluded that the pattern of this historical time configured the project of a defined society that remains in constant movement and change to preserve the dominant ideology that gave origin and support to it. If in the past, the obedience to the experts were the moral rule of the good hygienic citizenship, today citizens and families are reminded about the active attitude to preserve health and environment, as these collective goods could depend from the individual responsibility, no having in count the social determinants of iniquities in health.

O artigo tematiza os traços culturais e políticos do fenômeno da medicalização que se instituiu na sociabilidade brasileira por meio da moralização da família, nos moldes da ideologia higienista "cidadã". O estudo baseou-se na revisão de pesquisas historiográficas, contextualizando o surgimento da cidadania associada à forma como o higienismo, o saber especializado, sobretudo médico, e o controle social sobre a família, emolduraram perfis de indivíduos aptos à civilidade societária. Analisam-se os mecanismos do Estado para alinhar as políticas públicas emergentes à legitimação do modelo biologizante e seus reflexos na produção de conhecimentos ratificadores da ordem posta. Por fim, o artigo aborda as repercussões entre o passado e o presente e os dispositivos de afirmação da ideologia capitalista sobre a família brasileira, por meio da reatualização do fenômeno da medicalização. Conclui-se que o substrato desse tempo histórico configurou um projeto societário que permanece em movimento para a conservação do ideário que lhe deu origem e sustentação. Se, no passado, a obediência aos especialistas era o ícone da higiene-cidadã, atualmente cobra-se dos cidadãos e das famílias uma postura ativa na preservação da saúde e do ambiente como se esses bens coletivos estivessem ao alcance individual, desconsiderando os determinantes das iniquidades em saúde.
Metamorphoses of the social medicalization and its impacts on the Brazilian family
Keywords: medicalização; sociedade; eugenia; higiene; família; medicalization; eugenic; hygiene; family; society